The Schwartz Centre Rounds: Supporting mental health workers with the emotional impact of their work. (15th May 2020) - Allen, Deborah; Spencer, Graham; McEwan, Kirsten; Catarino, Francisca; Evans, Rachael; Crooks, Sarah; Gilbert, Paul
Abstract: In healthcare settings, there is an emotional cost to caring which can result in compassion fatigue, burnout, secondary trauma, and compromised patient care. Innovative workplace interventions such as the Schwartz Rounds offer a group reflective practice forum for clinical and non‐clinical professionals to reflect on the emotional aspects of working in health care. Whilst the Rounds are established in medical health practice, this study presents an evaluation of the Rounds offered to mental health services. The Rounds were piloted amongst 150 mental health professionals for 6 months and evaluated using a mixed‐methods approach with standardized evaluation forms completed after each Round and a focus group ( n  = 9) at one‐month follow‐up. This paper also offers a unique six‐year follow‐up of the evaluation of the Rounds. Rounds were rated as helpful, insightful, and relevant, and at six years follow‐up, Rounds were still rated as valuable and viewed as embedded. Focus groups indicated that Rounds were valued because of the opportunity to express emotions (in particular negative emotions towards patients that conflict with the professional care‐role), share experiences, and feel validated and supported by colleagues. The findings indicate that Schwartz Rounds offer a positive application in mental healthcare settings. The study supports the use of interventions which provide an ongoing forum in which to discuss emotions, develop emotional literacy, provide peer support and set an intention for becoming a more compassionate organization in which to work.